2011
DOI: 10.3109/1061186x.2010.511225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the tumor targeting of a FAPα-based doxorubicin prodrug

Abstract: Fibroblast activation protein-α (FAPα) is a tumor-associated antigen uniquely expressed by reactive stromal fibroblasts in the majority of human epithelial tumors. FAPα also possesses both post-prolyl peptidase and endopeptidase activities. Consequently, FAPα is increasingly considered as a potential pan-tumor target for designing tumor-targeted prodrugs. We previously conjugated Doxorubicin (Dox) with a FAPα-specific dipeptide (Z-Gly-Pro) to develop a FAPα-targeting prodrug of Dox (FTPD). The aim of current w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 30 publications
0
38
0
4
Order By: Relevance
“…Dicyclohexylcarbodiimide, N-hydroxysuccinimide, and N,N-Diisopropylethylamine (1:1:2, molar ratio) were then sequentially added into the DMSO solution. 32 The reaction mixture was stirred at 600 rpm at room temperature for 4 h in the dark. Finally, DOX-GEM was obtained via rotary evaporation method and purification by HPLC.…”
mentioning
confidence: 99%
“…Dicyclohexylcarbodiimide, N-hydroxysuccinimide, and N,N-Diisopropylethylamine (1:1:2, molar ratio) were then sequentially added into the DMSO solution. 32 The reaction mixture was stirred at 600 rpm at room temperature for 4 h in the dark. Finally, DOX-GEM was obtained via rotary evaporation method and purification by HPLC.…”
mentioning
confidence: 99%
“…27 The plasma cardiac output (Q co ) for rats was calculated as 2.69 L/hour. The mass balance equations (1)(2)(3)(4)(5)(6)(7)(8) for the model are shown as follows: …”
Section: Pbpk Modeling and Fittingmentioning
confidence: 99%
“…2 However, the insoluble nature of Z-GP-Dox becomes a significant barrier to drug administration, particularly when it comes to clinical trials. Therefore, it would be of great value to solve the solubility problem and achieve systemic delivery of this promising anticancer prodrug.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Huang et al [7] utilized the highly selective expression and the specific proteolytic activity of fibroblast activation protein-α (FAP-α) to construct a tumor targeting of FAP-α-based doxorubicin prodrug (Z-Gly-Pro-doxorubicin). It was found that FAP-α selective expressed on the surface of tumour-associated fibroblasts while not detected in normal adult tissues except tissues of healing wound [8].…”
mentioning
confidence: 99%